A molecular survey of three tick-borne pathogens in dogs from Algodoal village/Maiandeua island on the northeast coast of Pará, Brazil - David, Maridelzira Betânia Moraes; Pinheiro, Andrey Henrique Gama; Santana, Ricardo Luis Sousa; Castro, Marcela dos Santos; de Carvalho, Elaine Lopes; Gonçalves, Evonnildo Costa; Giese, Elane Guerreiro (Archives of Veterinary Science, 2023)
Ehrlichia spp., Anaplasma spp. and Babesia spp. are obligate intracellular parasitic microorganisms found in the blood of domestic animals. Until then, there were no reports of these hemoparasites in dogs in the northeast of the State of Pará. The aim of this study was to record cases of natural infection by Ehrlichia sp., Anaplasma sp. and Babesia sp. in dogs from Ilha de Algodoal/ Maiandeua, State of Pará, Brazil, through the detection of DNA from these agents. Whole blood samples were collected from 52 animals, without considering breed, sex or age. Include results for different species of animals and parasites. Molecular analysis data showed 50% co-infection for Ehrlichia sp. and Anaplasma sp. This study allowed the detection of Ehrlichia canis and Anaplasma platys in domestic dogs on Algodoal Island, an important ecological tourism site in northern Brazil.